Pengaruh Kepemimpinan Kepala Sekolah dan Kinerja Guru dan Motivasi Terhadap Prestasi Akademik Siswa Di UPTD SD Negeri Kecamatan Jeumpa Kabupaten Bireuen: Penelitian - Afria Liza; Alfi Syahrin; Sari Rizki (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the influence of school principals' leadership, teachers' performance, and motivation on students' academic achievement at UPTD SD Negeri in Jeumpa District, Bireuen Regency. The research employed a descriptive quantitative approach with an ex post facto design. Data were collected through questionnaires and analyzed using Pearson product-moment correlation and multiple linear regression. The results showed that school leadership had a moderate correlation with academic achievement at 40.3%. Teachers' performance influenced academic achievement by 53.9%, while motivation strengthened the relationship between teachers' performance and academic achievement by 57.8%, and directly influenced it by 51.4%. Obstacles identified included leadership assertiveness, teacher cohesiveness, and low work motivation.